Chapter 3. Impact of estrogens on hemostasis - Stanczyk, Frank Z.; Sriprasert, Intira; Chulapongwanich, Shinnisha; Yang, Jane L.; Fruzzetti, Franca (Frontiers in Endocrinology, 2025)
It is well established that estrogens increase the risk of both arterial and venous thrombosis. Abnormally high levels of some coagulation factors combined with a decrease in anticoagulation factors contribute to thrombotic risk. Although estrogens are known to affect multiple hemostatic markers, the exact molecular mechanism of estrogen-induced thrombosis is unclear. However, small changes in these markers with different types, doses, and/or routes of estrogens may increase thrombotic risk. Most studies on the effect of estrogens have been carried out in premenopausal women using combined oral contraceptives (COCs); studies in postmenopausal women using hormone therapy (HT) are scarce. Short-term studies comparing hemostatic parameters in women receiving either ethinyl estradiol (EE) or estradiol (E2), each combined with a different progestin, generally show that EE- and E2-based COCs have minimal hemostatic effects on most markers and weaker effects on some markers with E2. The novel estrogen estetrol (E4), emerging as a promising option for both hormonal contraception and postmenopausal HT, appears to have a neutral hemostatic effect. The increased procoagulant factors and decreased anticoagulatory mechanisms observed with estrogen use have been linked to an increased venous thromboembolism (VTE) risk and have been studied in women using hormonal contraception or HT. In contraceptive studies, it has been shown that estrogen dosage plays a role in VTE risk, as EE increases this risk in a dose-dependent manner. Although some studies suggest that the progestin type in COCs may affect VTE risk, other studies have found no difference in risk between androgenic and non-androgenic progestins. As for the E4-based COC, it is currently being evaluated for VTE risk in post-marketing studies. Regarding postmenopausal HT, both the CEE-alone and CEE/MPA arms of the Women’s Health Initiative trial showed an increased risk of VTE. However, the results are mixed regarding the impact of oral E2 on VTE risk. Although some data suggest a lesser impact of transdermal HT on this risk, further studies are needed to confirm this finding.